Investigating the flow dynamics and turbulence at a tidal-stream energy site in a highly energetic estuary. (August 2022) - Thiébaut, Maxime; Quillien, Nolwenn; Maison, Antoine; Gaborieau, Herveline; Ruiz, Nicolas; MacKenzie, Seumas; Connor, Gary; Filipot, Jean-François
Abstract: Measurements of an upward-looking Nortek Signature 1000 kHz five-beam acoustic Doppler current profiler are used to evaluate the mid-depth kinetic power density of the flow, energy-spectra of the velocity, turbulence intensity and an approximate turbulent kinetic energy budget at an estuarine tidal-stream energy site. The kinetic power density is 7 times higher during ebb tide than flood tide. Results reveal a strong influence of the bathymetry features and headland in the level of turbulence. A production-dissipation balance is demonstrated during the flooding stages of the tide whereas the ebbing stages of the tide exhibits a strongly unbalanced dissipation and production. Five (out of six) Reynolds stresses are calculated by the Dewey and Stringer's formulations which combine variances of the along-beam velocities, corrected from Doppler noise. The fifth beam of the Nortek Signature enables the direct (reference) measurement of the variances associated with the vertical flow direction thus offering the opportunity to test the validity of the Reynolds stresses derived from the Dewey and Stringer's formulations. The gap between the reference and the reconstructed variance associated with the vertical flow direction is found to be less than 5%.